تقييم نتائج استخدام المثبتات الخارجية (A.O) في علاج كسور الساق المفتوحة الناجمة عن الإصابات الحربية (أذيات المرامي النارية) - يوسف, صفوان; جوني, أحمد; راجح, ذي يزن (Latakia University Journal -Medical Sciences Series, 2018)
The main objective of the study is to apply external fixators (A.O) as an initial treatment until treatment is completed and evaluated to obtain the best therapeutic results, and to compare with available global studies. The study included patients with open tibial fractures (non-articular) resulting from war injuries in the ambulatory department at Al-Assad University Hospital and Tishreen University Hospital in Latakia and management by external fixators (A.O) from the beginning until the end of the treatment between 2012 and 2017. The study included 35 patients (39 cases), 31 of them males and 4 females aged between 20 and 58 years. (8 cases, 20.5%) were bullet and (31 cases, 79.4%) were hit by an explosive. Injuries were assessed according to the International Committee of the Red Cross (ICRC) classification. The major injuries were high-energy in 21 cases, 53.8%, massive injuries 13 cases, 33.3%, and low-energy cases in 5 cases, 12.8%. The mean duration of Healing was 24 weeks, while the functional results were good in 32 cases 82% and the accepted 5 cases 12.8% while the bad was in two cases 5.1%. We conclude from the study that external fixation is an important and very good option in managing open fractures caused by war injuries if not the best and only option to manage such injuries in a safe and easy method. الهدف الأساسي من الدراسة هو تطبيق المثبتات الخارجية (A.O) كعلاج بدئي وحتى إنهاء العلاج والتقييم للحصول على النتائج العلاجية الأفضل، والمقارنة مع الدراسات العالمية المتوفرة. شملت الدراسة مرضى كسور الساق المفتوحة (غير المفصلية) الناجمة عن المرامي النارية المراجعين لقسم الإسعاف في مشفى الأسد الجامعي ومشفى تشرين الجامعي في اللاذقية والمعالجين بالمثبتات الخارجية من نوع (A.O) من البداية حتى انتهاء العلاج في الفترة بين 2012 وحتى 2017. شملت الدراسة 35 مريض (39 اصابة) 31 منهم ذكور و4 اناث تراوحت أعمارهم بين 20 و58 سنة. (8 حالات 20.5%) كانت اصابتهم بطلق ناري و (31 حالة 79.4%) كانت اصابتهم بأذية انفجارية. تم تقييم الإصابات حسب تصنيف اللجنة الدولية للصليب الأحمر(ICRC) وكانت اغلبية الإصابات عالية الطاقة 21 حالة 53.8% والاصابات الجسيمة 13 حالة 33.3% بينما منخفضة الطاقة كانت في 5 حالات 12.8%. متوسط فترة الاندمال كانت 24 أسبوع بينما النتائج الوظيفية كانت جيده لدى 32 حالة 82% والمقبولة 5 حالات 12.8% بينما السيئة كانت لدى حالتين 5.1%. استنتجنا من الدراسة ان التثبيت الخارجي خيار مهم وجيد جدا في تدبير الكسور المفتوحة الناجمة عن الإصابات الحربية ان لم يكن هو الخيار الأفضل والوحيد لتدبير مثل هذه الإصابات وبشكل أمن وسهل.